P298 Risk factors for the progression of non-alcoholic fatty liver disease in people with inflammatory bowel disease. (30th January 2023) - Walker, C; Dempsey, M; Connaughton, R; Carroll, A; Breslin, N; McNamara, D; O'Donnell, S; Ryan, B; O'Connor, A
Abstract: Background: Non-alcohol fatty liver disease (NAFLD) is one of the most common liver disorders, and occurs more frequently in people with inflammatory bowel disease (IBD). Previous research suggests that increased age, BMI, and IBD duration, previous bowel resection, and co-morbid diabetes are risk factors for the development of NAFLD with IBD. Our aim was to investigate possible risk factors for the progression of NAFLD in people with IBD. Methods: A prospective single centre cohort study. In total, we recruited 203 patients from the IBD service of our tertiary, academic centre. 7 participants were excluded due to later diagnosed non-NAFLD liver disease. Following informed consent, participants underwent a fibroscan and blood tests for liver function tests and a FIB-4 and score were taken. Basic demographics, information about IBD, exercise measured on the Godin-Shepard Leisure Time Physical Activity Questionnaire, LFTs, FIB4 score, controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) were recorded. T-test, Fishers exact, and Pearson's correlation coefficient were used to test for statistical significance as appropriate. Results: Of the 196 IBD patients included, 16.3% (n=32) had a CAP score >294dB/m consistent with NAFLD, and 2.6% (n=5) had a LSM >8.1kPa consistent with fibrosis. Only 40.6% of those with NAFLD (n=13/32), had abnormal liver enzymes. In regards to FIB 4 score, 8.1% (n=8/91) of those without NAFLD had a FIB4 score >1.3, none with NAFLD alone, and 50% (n=2/4) of those with fibrosis. We found a positive correlation between BMI and waist circumference with CAP score, Pearson's r= 0.514 and 0.536 respectively. In those with NAFLD, the fibrosis group had higher BMIs and waist circumferences, 37.44 vs 31.44 (p=0.0265) and 108.6cm vs 107.6cm (p=0.0781) respectively, than the NAFLD without fibrosis cohort. They also had a higher alcohol intake in units/week (21 vs 4.1 p=0.0204), smoking pack year history (31.66 vs 23.63 p=0.482), and HbA1c (6.36% vs 5.76% p=0.108) and had lower exercise scores (0.6 vs 20.1 p=0.0186). Longer IBD disease duration, biologic therapy, anti-TNF therapy, azathioprine, previous surgery, or extra-intestinal IBD did not seem to affect those who developed fibrosis. Conclusion: The development of fibrosis secondary to NAFLD in people with IBD seems to be driven by metabolic risk factors rather than related to IBD. A high index of suspicion for IBD patients with a high BMI even without deranged LFTs, should lead to consideration for fibroscan. Further research is needed on whether FIB-4 scoring has utility in the IBD population.